Carbon Nanotubes Characterization by X-ray Powder Diffraction – A Review - Das, Rasel; Bee Abd Hamid, Sharifah; Eaqub Ali, Md.; Ramakrishna, Seeram; Yongzhi, Wu (Current Nanoscience, 2015)
Carbon nanotubes have been increasingly used in the fields of nanorobotics, electrochemical catalysis, microarray chips, and green adsorbents for pollutants, sensors and optoelectronics. Complicated physico-chemical aspects and novel schemes to synthesize controlled featured carbon nanotubes have added new ambiguities to their characterizations and applications and these must be resolved on an urgent basis. Most of the characterization tools such as scanning electron microscopy, transmission electron microscopy, scanning tunneling microscopy and atomic force microscopy probes only for characterizing the local features of carbon nanotubes. However, X-ray powder diffraction can reveal the local and global features of microstructure’s lattice and crystalline phases, domain sizes, and impurities. Thus it is worthwhile to highlight this technique for better understanding and utilization of its benefit to unravel the carbon nanotube ambiguities. To the best of our knowledge, no comprehensive reviews or systematic description of X-ray powder diffraction on carbon nanotubes characterization have been published yet. In this review, we filled-up this gap and provided a systematic presentation of X-ray powder diffraction application in carbon nanotubes characterization. This could be used as a reference guide for the utilization of X-ray powder diffraction to probe the various features of carbon nanotubes and carbon nanotubes based materials.
Keywords: structure